The Effect of Physical Activities on the Fitness Levels in Children with Developmental Problems/Impaired Development - Ķīsis, Igors; Sitņika, Nataļja (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
Physical activities have for long been seen as one of the most effective tool of aiding correct growth and development of children. Worldwide children have become a lot less physically active and this is even more apparent in less developed regions. The time and resources devoted to physical education and activities continue to decrease as physical activities and sports games are increasingly being substituted with computer and console games, as well as TV programs. By analyzing the results of EUROFIT method in 2010 it has been found that in all institutions of general secondary education, 47.5% of boys and 55.5% of girls had shown fitness levels below the average level, but 12.8% of boys and 15.1% of girls were seen to have fitness levels being at a low level. As seen in many scientific treatises, every member of society needs to be capable of maintaining a healthy lifestyle in order to ensure optimum health and fitness levels. Regular physical activities improve all components of overall fitness, whereas a precondition to good health is to regularly perform daily activities along with extra physical activities such as sports, and thus having a good overall level of fitness.